Correlation of living will, bioethics, professional activity and patient autonomy - Silva Pirôpo, Uanderson; Oliveira Damasceno, Rudson; Souza Rosa, Randson; Lago da Silva Sena, Edite; Donha Yarid, Sérgio; Silva de Oliveira Boery, Rita Narriman (Universidad Nacional de Colombia, 2018)
Objective To analyze the correlation between living will and bioethical aspects, professional performance and patient autonomy. Methods Theoretical reflection after a search conducted in the Virtual Health Library, PubMed and SciELO databases, using the words living will, right of the patient, bioethics, personal autonomy and health professional, as well as the corresponding terms in Portuguese. Based on the reading, abstracts that met the proposed objective were selected and full texts were subsequently consulted and read critically to support this reflection. Results Analyzes led to reflect on bioethics applied to health professional knowledge on the rights of terminally ill patients, as well as their autonomy regarding their living will. Conclusion Living will is still a poorly understood term that needs greater dissemination and knowledge among health professionals and the population, as it addresses the legitimacy of patient's rights at a crucial moment of human life.
Relación entre testamento vital, bioética, actuación profesional y autonomía del paciente
Interface do testamento vital com a bioética, atuação profissional e autonomia do paciente
Keywords: Bioethics; Health personnel; Living wills; Personal autonomy